Analysis of Legal Certainty Regarding the Fulfilment of The Element of Intentional and Negligence in Corporate Criminal Liability - Leonardo Alfero; Mella Ismelina F. Rahayu (Borong Newinera Publisher, 2024)
In cases related to environmental damage, corporations are considered as legal subjects that can be held responsible if they have intentionally or negligently carried out their obligations, related to errors committed by corporations, the study of the fulfillment of the elements of intentionality and negligence is a problem of legal certainty in handling cases that use legal basis Article 98 or Article 99 of Law Number 32 of 2009 concerning Environmental Protection and Management. The research method used is normative legal research. The approaches used are the statutory approach and the comparative approach. The data analysis technique is deductive analysis. After analysis, a conclusion was determined, namely the fulfillment of the elements of intentionality and negligence in the UUPPLH, including first, the element of every person, meaning an individual or business entity, secondly, the element of deliberate or negligence as an element of an environmental offense, related to intention or inner attitude (mens rea). from the perpetrator of the crime. Third, the element of the act is no longer emphasized that the act is against the law (wederrechtelik, unlawful). Fourth, elements resulting in exceeding ambient air quality standards, water quality standards, sea water quality standards, or environmental damage standard criteria. Furthermore, in criminal liability, corporations are legal subjects that can be held responsible for their mistakes, whether intentional or negligent, based on Article 98 and Article 99 of the UUPPLH with the threat of penalties for intentional offenses that are more severe than for offenses of negligence.